2001
DOI: 10.1521/psyc.64.3.202.18462
|View full text |Cite
|
Sign up to set email alerts
|

Television Exposure in Children after a Terrorist Incident

Abstract: This study examined the influence of bomb-related television viewing in the context of physical and emotional exposure on posttraumatic stress symptoms--intrusion, avoidance, and arousal--in middle school students following the 1995 Oklahoma City bombing. Over 2,000 middle school students in Oklahoma City were surveyed 7 weeks after the incident. The primary outcome measures were the total posttraumatic stress symptom score and symptom cluster scores at the time of assessment. Bomb-related television viewing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(205 citation statements)
references
References 40 publications
13
188
1
3
Order By: Relevance
“…Recent survey data indicate that 36% of American children under the age of 6 have their own television in their bedroom (Rideout et al, 2003). After Oklahoma City and 9/11, television exposure in children was associated with more post-traumatic stress symptoms, at least in the short term (Pfefferbaum et al, 2001; NYC Board of Education, 2002). Some teachers in Oklahoma City chose to forego class activities in favor of watching live reports on television in the classroom.…”
Section: Terrorism Risk and Interventions: A Developmental Resiliencementioning
confidence: 99%
“…Recent survey data indicate that 36% of American children under the age of 6 have their own television in their bedroom (Rideout et al, 2003). After Oklahoma City and 9/11, television exposure in children was associated with more post-traumatic stress symptoms, at least in the short term (Pfefferbaum et al, 2001; NYC Board of Education, 2002). Some teachers in Oklahoma City chose to forego class activities in favor of watching live reports on television in the classroom.…”
Section: Terrorism Risk and Interventions: A Developmental Resiliencementioning
confidence: 99%
“…Television coverage has also been implicated. [16][17][18][19][20] Combined forms of exposure may increase risk. For example, March and colleagues 11 found that posttraumatic stress symptomatology resulted from direct visual exposure and from indirect exposure through nonwitnessed harm to relatives and/or close friends in children 9 months after exposure to an industrial fire.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,[14][15][16][17][18][21][22][23] Nader and colleagues 17 found that PTSD symptomatology in Kuwaiti children following the Gulf War correlated positively with direct exposure through witnessing and with indirect exposure through television coverage, but not with indirect exposure through interpersonal relationships. On the other hand, in a study of the impact of various forms of trauma, illness or death of someone close to the child posed the greatest risk for the development of PTSD, 14 and interpersonal exposure was more important than physical exposure in adolescents who witnessed a school bus accident involving their peers.…”
Section: Introductionmentioning
confidence: 99%
“…It does appear, however, that news consumption is related to temporary increases in anxiety in the general adult public. Children, however, appear to be equally affected by news coverage, regardless of the extent of their involvement in the disaster (Pfefferbaum et al, 2001).…”
Section: Population Level Issues: Communicationmentioning
confidence: 95%